The Application of Brain-Based Learning in Teaching Reading Comprehension to The First Year Students of MA As'adiyah Ereng-Ereng Bantaeng - Muh Agus Nur; Ruslan Hasyim; Ahsanul Khalikin (Qalam : Jurnal Ilmu Kependidikan, 2020)
The objective of this research described the application of Brain-Based learning to be used in teaching reading comprehension to the first year students of MA As’adiyah Ereng-Ereng Bantaeng Regency. The method was used by the research was descriptive quantitative method. The variables of this research were independent variable (the application of Brain Based Learning) and dependent variable (Teaching Reading Comprehension). The population of this research was the first year students of MA As’adiyah Ereng-Ereng Bantaeng Regency in academic year 2010/2011.The total number of population was 22 students. The sample of the research was 22 students which were taken by using total sampling technique. The instrument of this research was reading comprehension test. The result of the data indicated that there was a good classification. The mean score of post-test was (80) and standard deviation in post-test was 9.1. Based on the finding and discussion of the research, the researcher drawn a conclusion that the application of Brain Based Learning was good to be used in teaching reading comprehension to first year students of MA As’adiyah Ereng-Ereng.